Congeneric mutualist ant symbionts (Tetraponera, Pseudomyrmecinae) differ in level of protection of their myrmecophyte hosts (Barteria, Passifloraceae). (29th July 2019) - Kokolo, Bertrand; Atteke, Christiane; Mintsa, Boris Achille Eyi; Ibrahim, Brama; McKey, Doyle; Blatrix, Rumsais
Abstract: Barteria fistulosa and B. dewevrei, central African rain-forest trees, provide nesting cavities for Tetraponera aethiops and T. latifrons ants, respectively, which protect them against herbivores. To compare protection efficiency between these two symbioses, for 20 plants of each species in two sites in Gabon we measured the time elapsed before ants reached a focal leaf, for host leaves that were undisturbed, damaged (cut with scissors) or subjected to slight vibration (mimicking such damage), and for damaged leaves of the non-host Barteria species. Tetraponera aethiops displayed stronger protective behaviour than did T. latifrons . Time to reach a damaged host leaf (4.5 ± 2.6 min, mean ± SD) did not differ significantly from time to reach a leaf subjected to slight vibration (5.2 ± 3.0 min) for T. aethiops, but response to a leaf subjected to slight vibration (9.5 ± 1.9 min) was significantly slower than that to a damaged leaf (7.8 ± 1.9 min) for T. latifrons . The faster response of T. aethiops to slight vibration may have masked a response of this species to chemical signalling. Both ants reached damaged host leaves faster than damaged leaves of the non-host Barteria sp., indicating host plant specificity in ant responses.